Kriterium Majmuk bagi Penganggaran Parameter dan Peramalan Sambutan - Haron, Kassim (1992)
A multiplicative compound criterion is used to generate a unique design which can simultaneously fulfil two important objectives: parameter estimation and response prediction. Thegene ralised variance criterion is chosen for the first objectivec while the variance function or the integrated variance criterion is fOr the second.